2013
DOI: 10.1007/s11695-013-1010-3
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Surgery Smartphone Apps: a Review

Abstract: This study has identified that the majority of available apps relating to weight loss surgery do not have health professional input. The establishment of a 'quality stamp' provided by an established bariatric surgical body could improve the confidence with which patients and clinicians use these new information sources. Weight loss surgery apps offer a unique opportunity to provide accurate and reliable patient information and their use as part of the informed consent process should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…No studies were found which explored the use of social media with bariatric surgical patients. A review of 38 smartphone apps for weight-loss surgery found no healthcare professional input and called for a 'quality stamp' from bariatric surgical bodies (8). This finding is congruent with the concerns about the quality of information on mobile apps expressed by the respondents in this survey.…”
Section: Introductionsupporting
confidence: 64%
“…No studies were found which explored the use of social media with bariatric surgical patients. A review of 38 smartphone apps for weight-loss surgery found no healthcare professional input and called for a 'quality stamp' from bariatric surgical bodies (8). This finding is congruent with the concerns about the quality of information on mobile apps expressed by the respondents in this survey.…”
Section: Introductionsupporting
confidence: 64%
“…This suggests that a patient-centred, jointly designed app for bariatric patients could be a valuable clinical tool. The proliferation of mHealth apps provide consumers with extensive choice; however, because earlier studies have emphasised these often do not contain evidencebased content and have potential to compromise patient care as a result of a lack of input from health professionals in their design (16,17) . It is important for dietitians to not only be aware of digital disruption, but also be actively involved in shaping the use of technologies to enhance patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have acknowledged that apps are becoming an accepted part of a dietitian's toolkit (18) ; however, dietitians specialising in the support of bariatric patients have not been previously surveyed specifically to determine their requirements, nor have the patients themselves. Bariatric-specific smartphone apps that have been examined to assess adherence to evidence-based practice, clinical rigor and health professional input did not focus on the nutrition monitoring needs of dietitians (16,17) . In the present study, dietitians and bariatric patients were forthcoming with suggestions for features that they would find helpful in mHealth apps.…”
Section: Discussionmentioning
confidence: 99%
“…The store owner offers toolkits (software development kits (SDK)) to their developers that facilitate user participation by creating an ecosystem for development (Franke and von Hippel 2003;von Hippel 2001 Recently, analytics data such as user ratings and smartphone app prices have already been investigated in different medical disciplines, such as obesity (Stevens et al 2014), orthopedics (Franko and Bhola 2011), hernia repair (Connor et al 2013), and surgery (O'Neill and Brady 2012;Dala-Ali et al 2011). To our best knowledge, ours is the first attempt to identify user innovations in the field of medical smartphone apps.…”
Section: Empirical Field: E-health M-health and Medical Smartphone mentioning
confidence: 99%